Beta alanine supplementation effects on metabolic contribution and swimming performance - Silva Norberto, M.; Barbieri, R. A.; Rodrigues Bertucci, R.; Bucken Gobbi, R.; Zapaterra Campos, E.; Moura Zagatto, A.; De Freitas, E. C.; Papoti, M. (Journal of the International Society of Sports Nutrition, 2020)
Background: Investigations of ß-alanine supplementation shows effects on metabolic (aerobic and anaerobic) participation and performance on swimming by a possible blood acidosis buffering. Considering this background, the objective of the present study was to analyze the effects of ß-alanine supplementation on metabolic contribution and performance during 400-m swim. Methods: Thirteen competitive swimmers underwent a 6-week, double-blind placebo-controlled study, ingesting 4.8 g.day- 1 of ß-alanine or placebo. Before and after the supplementation period, the total anaerobic contribution (TAn) and 30-s all-out tethered swimming effort (30TS) were assessed. Anaerobic alactic (AnAl) and lactic energy (AnLa) was assumed as the fast component of excess post-exercise oxygen consumption and net blood lactate accumulation during exercise (?[La-]), respectively. Aerobic contribution (Aer) was determined by the difference between total energy demand and TAn. In addition to conventional statistical analysis (Repeated measures ANOVA; p > 0.05), a Bayesian repeated measures ANOVA was used to evidence the effect probability (BFincl). Results: No differences and effects were found between groups, indicating no supplementation effects. Repeated measures ANOVA, with confirmation of effect, was indicate reduce in DeltaLactate (p: 0.001; BFincl: 25.02); absolute AnLa (p: 0.002; BFincl: 12.61), fatigue index (p > 0.001; BFincl: 63.25) and total anaerobic participation (p: 0.008; BFincl: 4.89). Conclusions: Thus, the results demonstrated that all changes presented were evidenced as a result of exposure to the training period and ß-alanine supplementation doesn`t affect metabolic contribution and performance during 400-m freestyle.